«To be read poco a poco»: a letter from Edward Dubois (1774-1850) to Francis Douce (1757-1834) - Cerón, Mercedes (Cuadernos de Ilustración y Romanticismo, 2023)
This article focuses on a letter signed «ED» found among the papers of the British antiquary Francis Douce (1757-1834) and kept in the Bodleian Library in Oxford. The identity of Douce’s anonymous correspondent is discussed, a hypothesis regarding both authorship and date is proposed, and the contents of the letters are explored in connection with the transmission of knowledge within Douce’s extended networks, paying particular attention to his Spanish acquaintances and correspondents.